1998
DOI: 10.1046/j.1365-8711.1998.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of far-infrared emission from edge-on galaxies

Abstract: We use resolution‐enhanced IRAS images (HiRes) to study the distribution of far‐infrared (FIR) emission in 20 edge‐on, disc galaxies. Half of our sample are selected as infrared‐bright galaxies which emit most of their energy at wavelengths longer than a few μm. The remaining 10 objects are ‘normal’ (quiescent) galaxies. The distribution of FIR emission along the major axis of the infrared‐bright galaxies tends to be far more centrally concentrated than that detected in quiescent discs. Indeed, many of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 18 publications
6
36
0
Order By: Relevance
“…The ISOPHOT data at 100 and 200 µm give a better measure of the dust temperature. T dust determined for the ISOPHOT sample, as well as for 6 quiescent galaxies observed with ISOPHOT by Alton et al (1998) consistently with Contursi et al (2001), seems to be independent of the UV radiation field as traced by the Hα + [NII]EW, of the metallicity or of the total luminosity. The average value is T dust = 20.8 ± 3.2 K, which we will assume also for galaxies without ISOPHOT measurements.…”
Section: An Alternative Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…The ISOPHOT data at 100 and 200 µm give a better measure of the dust temperature. T dust determined for the ISOPHOT sample, as well as for 6 quiescent galaxies observed with ISOPHOT by Alton et al (1998) consistently with Contursi et al (2001), seems to be independent of the UV radiation field as traced by the Hα + [NII]EW, of the metallicity or of the total luminosity. The average value is T dust = 20.8 ± 3.2 K, which we will assume also for galaxies without ISOPHOT measurements.…”
Section: An Alternative Methodssupporting
confidence: 58%
“…Unfortunately only integrated HI and dust masses are available for our spatially unresolved galaxies. It is however reasonable to assume that the cold dust is as extended as the optical disc (Alton et al 1998). The HI gas surface density is available only for a few galaxies in our sample from VLA observations (Cayatte et al 1994).…”
Section: An Alternative Methodsmentioning
confidence: 99%
“…According to Alton et al (1998), we interpret the steady increase in the surface brightness scale-length from 70 to 500 µm as the result of a cold-dust temperature gradient with galactocentric distance combined with a scale-length of the dust disk larger Notes. * Curve not fitted by an exponential fit within the selected range in radius; ** Profile not available.…”
Section: Discussion and Comparison With The Literaturementioning
confidence: 93%
“…With higher resolution Spitzer observations of 57 galaxies in the SINGS sample, Muñoz-Mateos et al (2009a) instead found that the distribution of the dust mass (derived from SED fits up to the longest available wavelength of 160 µm; FWHM = 38 ) has a similar scale-length to that measured for stellar emission at 3.6 µm. However, the result is not incompatible with that of Alton et al (1998), since near-IR (NIR) surface brightness profiles are steeper than in the optical.…”
Section: Introductionmentioning
confidence: 80%
“…On the other hand, bright sources above 200 mJy with a red color could be dominated by very luminous galaxies such as Arp 220 at moderate redshifts. In addition, there may be a contribution from galaxies having very cold dust (Alton et al 1998;Haas et al 1998). The large errors associated with the flux calibration hampers further insight into the flux-color diagrams.…”
Section: Ir Colorsmentioning
confidence: 99%